PEMANFAATAN MEDIA WORD SQUARE DALAM PENGEMBANGAN LEMBAR KERJA SISWA (LKS) KOMPETENSI MENULIS PENUTUR ASING - Mayrita, Hastari (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2018)
Teaching materials is a thing that is needed by learners, especially foreign speakers who learn Indonesian. Teaching materials can also be used by Indonesian teachers to facilitate learning Indonesian language for foreign speakers. Teaching materials developed by researchers to facilitate the process of foreign speakers is LKS Bahasa Indonesia One of the teaching materials developed by researchers to facilitate the process of foreign speakers is LKS Indonesian Language people Foreign. LKS developed by researchers through this paper is LKS Writing Competency for Beginner BIPA Students. LKS developed by researchers based on word square learning model. Word square learning model is one of the contextual learning models that use media box answers. The problem in this research is how the needs of BIPA Beginner students and teachers in writing lessons that serve as learning materials development. The subject of this research is all BIPA students of Bina Darma University.